Os desafios na alfabetização: dos fundamentos ao fazer pedagógico - ARAÚJO, Claudiane Nunes (2019)
The present work aims at reflecting and analyzing the challenges of literacy, seeking the theoretical underpinnings of Ferreira and Teberosky (1999), Cagliari (2006, 2009), Magda Soares (2010), Kramer (2010) and Mendonça (2011). ), Morais (2012), relating the practices about practices and concepts of some literacy teachers who work in the first year of primary education in the municipality of Castanhal-Pa. A field survey was carried out with twenty-five literacy teachers, using a structured model from nine semi-open questions. The statements were about the tendencies and practices of literacy in Brazil: as basic concepts; a "disincentive" of literacy and a "reinvention" of literacy. It was possible to analyze from the previous date for the foundations and the pedagogical practices evidenced in literacy in the Municipal Network of Education of Castanhal-PA.